Let g(x) be the reflection of f(x) = x2 +3 in the x-axis. What is the function rule for g(x)? A. g(x) = -x2 - 3 B. g(x) = -x2 + 3 C. g(x) = x2 - 3 D. g(x) = x2 + 3

Let g(x) be the reflection of f(x) = x2 +3 in the x-axis. What is the function rule for g(x)? A. g(x) = -x2 - 3 B. g(x) = -x2 + 3 C. g(x) = x2 - 3 D. g(x) = x2 + 3

Let g(x) be the reflection of f(x) = x2 +3 in the x-axis. What is the function rule for g(x)? A. g(x) = -x2 - 3 B. g(x) = -x2 + 3 C. g(x) = x2 - 3 D. g(x) = x2 + 3

Original conversation

User: solve the equation 2=2(x-2)+2-x

User: Let g(x) be the reflection of f(x) = x2 +3 in the x-axis. What is the function rule for g(x)? A. g(x) = -x2 - 3 B. g(x) = -x2 + 3 C. g(x) = x2 - 3 D. g(x) = x2 + 3

Weegy: The answer is A. g(x) = -x2 - 3 dennis003|Points 1030|

User: Write The ratio 1 3/4 to 4 3/4 as a fraction in lowest terms

User: Can you tell the angle measures of a triangle?

User: What is the solution for x? 2x + y = 1 4x + 2y = -1

2x + y = 1, multiply 2 on both sides: 4x + 2y = 2 (the first equation) 4x + 2y = -1(the second equation) Subtracting the first and the second equations: 0 = 3 which is a false statement, therefore, there is NO SOLUTION for the system of equations 2x + y = 1, 4x + 2y = -1

There are no comments.